The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00213-012-2652-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ecstasy/polydrug use on memory for associative information

Abstract: Rationale. Associative learning underpins behaviours that are fundamental to the everyday functioning of the individual. Evidence pointing to learning deficits in recreational drug users merits further examination. Objectives. A word pair learning task was administered to examine associative learning processes in ecstasy/polydrug users. Methods. Conclusions. Overall, the results suggest that long-term ecstasy exposure may induce a deficit in associative learning and this may be in part a consequence of users a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In 2012, another study observed more false-positive responses of ecstasy/polydrug users than nonusers [95]. Increased long-term frequency of ecstasy use was positively associated with memories when ingested before encoding.…”
Section: Dopaminergic and Other Neurotransmitter System Modulation Of False Memoriesmentioning
confidence: 98%
“…In 2012, another study observed more false-positive responses of ecstasy/polydrug users than nonusers [95]. Increased long-term frequency of ecstasy use was positively associated with memories when ingested before encoding.…”
Section: Dopaminergic and Other Neurotransmitter System Modulation Of False Memoriesmentioning
confidence: 98%
“…The studies were published between 1989 and 2021, with the following distribution per publication year: one study each year in 2021 (Cuttler et al, 2021), 2019 (Kloft et al, 2019), 2017 (Brion et al, 2017), 2015 (Riba et al, 2015), 2014 (Fisk et al, 2014), 2013 (Klein et al, 2013), 2011 (Maurage et al, 2011), 2003(Rocha and Albuquerque, 2003(Fox et al, 2001, 2000 (Gudjonsson et al, 2000), 1997 (Welch et al, 1997(Kramer et al, 1989; and two studies each year; in 2012 (Gallagher et al, 2012;Henry et al, 2012(Schilt et al, 2008Thoma et al, 2008(Gudjonsson et al, 2004Reich et al, 2004).…”
Section: Datementioning
confidence: 99%
“…Six of the 18 studies were conducted in the United States (Kramer et al, 1989;Welch et al, 1997;Reich et al, 2004;Henry et al, 2012;Klein et al, 2013;Cuttler et al, 2021), three in the United Kingdom (Fox et al, 2001;Gallagher et al, 2012;Fisk et al, 2014), two in Iceland (Gudjonsson et al, 2000(Gudjonsson et al, , 2004, two in the Netherlands (Schilt et al, 2008;Kloft et al, 2019), and another two in Belgium (Maurage et al, 2011;Brion et al, 2017). The remaining three studies were conducted in the following countries: Portugal (Rocha and Albuquerque, 2003), Germany (Thoma et al, 2008), and Spain (Riba et al, 2015).…”
Section: Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…Fox et al, 2001; Kalechstein et al, 2007; Schilt et al, 2007; Zakzanis et al, 2007). Other aspects of memory function reportedly affected by ecstasy use include reduced initial encoding levels, impaired use of strategy during encoding, and poor performance on more complex learning and recall tasks (Brown et al, 2010; Gallagher et al, 2012; Montgomery et al, 2007, 2010; Quednow et al, 2006). These types of impairment support a developing theory that implicates frontostriatal network dysfunction in ecstasy-induced neurocognitive impairment (Bosch et al, 2013; Quednow et al, 2006).…”
Section: Introductionmentioning
confidence: 99%